Worldwide regulations and policy trends on gas production from gas hydrates - Merey Sukru; Chen Lin (Science and Technology for Energy Transition, 2023)
Gas hydrates are considered near-future energy resources with their vast amounts all around the world, especially in permafrost and marine environments. Since the beginning of the 2000s, there have been many gas hydrate exploration, drilling, coring, and production trials in the world. The countries (i.e., Japan, China, India) that need urgent energy resources are in a rush to produce feasible natural gas from gas hydrate reservoirs. However, according to available production trial data, there are many obstacles to reaching the commercial level of gas production. Due to the sensitive nature of gas hydrate reservoirs, the health, safety, and environmental risks of all production trials should be discussed. Moreover, it is crucial to control the risks of these production trials. This study aims to investigate the worldwide regulations and policy trends related to gas hydrate production trials.